Innovation in Blended Learning: A Solution to the Shortage of Computer Laboratories in Information, Communication, and Technology Courses - Sagiman Sagiman; Laras Shesa; Muhammad Istan; Ruly Morganna (LP. Ma'arif Janggan Magetan, 2026)
Advances in digital technology have created substantial opportunities for instructional innovation, particularly in higher education institutions facing limitations in physical facilities such as computer laboratories. This study aims to develop and evaluate the effectiveness of a blended learning model supported by Google Classroom as a solution to the shortage of computer laboratories in the Information and Communication Technology course. The research method employed was research and development with an instructional design approach based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observations, interviews, questionnaires, and analysis of student performance within the blended learning environment. The findings revealed that the blended learning model not only enhanced students’ learning independence but also improved teaching effectiveness by optimizing digital resources. Moreover, the implementation of Google Classroom provided flexibility in accessing materials, facilitated more dynamic interaction, and reduced the operational burden on computer laboratories. The novelty of this research lies in the integration of digital instructional strategies with the specific needs of faith-based higher education institutions, which remain underexplored in the higher education literature. Accordingly, this study contributes to the development of adaptive instructional models that can be applied in other educational institutions facing similar infrastructural constraints.